2023
DOI: 10.1532/hsf.5087
|View full text |Cite
|
Sign up to set email alerts
|

The Preoperative Uric Acid-to-Albumin Ratio as a New Indicator to Predict Long-Term Prognosis After Surgery for Patients with Acute Type A Aortic Dissection

Abstract: Background: The long-term prognosis of patients with acute type A aortic dissection (AAD) is poor, despite emergency surgical treatment. Therefore, it is imperative to evaluate patient risk factors to improve the prognosis. The aim of this study was to analyze the ability of the uric acid-to-albumin ratio (UAR) to predict the long-term mortality of patients with type A AAD after surgery. Methods and results: A total of 289 patients with type A AAD who had received surgical treatment was enrolled in this study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Zhang et al constructed Nomogram images in the perioperative period to predict acute kidney injury after ATAAD [ 42 ]. Wang et al demonstrated that the uric acid-to-albumin ratio was an independent predictor for long-term mortality of patients with ATAAD (sensitivity = 69.6%, specificity = 51.8%) [ 43 ]. These results indicate that the search for effective serologic markers is of great importance for the diagnosis and prognosis prediction of ATAAD and is also the foci of ATAAD research in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al constructed Nomogram images in the perioperative period to predict acute kidney injury after ATAAD [ 42 ]. Wang et al demonstrated that the uric acid-to-albumin ratio was an independent predictor for long-term mortality of patients with ATAAD (sensitivity = 69.6%, specificity = 51.8%) [ 43 ]. These results indicate that the search for effective serologic markers is of great importance for the diagnosis and prognosis prediction of ATAAD and is also the foci of ATAAD research in the future.…”
Section: Discussionmentioning
confidence: 99%